The Potential Contribution of Earth Observation Data Cubes for the Production of Information for Sustainable Development in Emerging Countries - Merodio Gómez, Paloma; Ramírez Santiago, Andrea; Juárez Carrillo, Olivia Jimena; Jiménez Nava, Francisco Javier (Geomatics and Environmental Engineering, 2022)
One of the great challenges of achieving the shared vision of the 2030 Agenda for Sustainable Development is having high-quality, timely, comparable, and accessible data that allows to measure and report progress on the Sustainable Development Goals (SDG). Hence, in many countries, geospatial information (including Earth observation) and algorithms implemented in cloud computing platforms have become important tools to monitor indicators of the SDG thanks to their broad accessibility and global coverage. However, emerging countries still face barriers to the implementation of technologies to manage the large amounts of EO data. This article aims to show the advantages of satellite-based EO in the measurement of SDG indicators, as well as challenges emerging countries face in the use of these technological tools. It addresses why the open-source tool Open Data Cube (ODC) should be seen as a response to the said challenges. Finally, there is a description regarding the experience of Mexico with the use and application of this tool for the measurement of SDG indicators, from the development and implementation of the Mexican Geospatial Data Cube (MGDC) to the results obtained from its application in the support for the measurement of SDG indicators 6.6.1 Change in the extent of water-related ecosystems over time and 15.1.1 Forest area as a proportion of total land area.